2011
DOI: 10.1091/mbc.e10-10-0849
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma motility occurs in the absence of actin polymer

Abstract: Human glioblastoma cells are motile in the absence of intact actin polymers, following suppression of actin assembly by specific inhibitors. On the other hand, suppression of microtubules completely blocks motility. These results are clearly divergent from the standard model of actin-based cell motility in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
5
35
0
Order By: Relevance
“…The gradient of Rho-family GTPase activity within the glioblastoma tissue strongly supports the idea that the two glioblastoma invasion modes are correlated with the activities of Rho-family GTPases. Interestingly, recent studies by Panopoulos et al showed that mesenchymal migration of glioblastoma cells does not require Rac1 activity on 2D substrates (Panopoulos et al, 2011). This observation suggests that glioblastoma cells do not require Rac1 activity to move without marked resistance on dishes or around blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The gradient of Rho-family GTPase activity within the glioblastoma tissue strongly supports the idea that the two glioblastoma invasion modes are correlated with the activities of Rho-family GTPases. Interestingly, recent studies by Panopoulos et al showed that mesenchymal migration of glioblastoma cells does not require Rac1 activity on 2D substrates (Panopoulos et al, 2011). This observation suggests that glioblastoma cells do not require Rac1 activity to move without marked resistance on dishes or around blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Restructuring of the cytoskeleton is imperative in the process of cell proliferation and in migration and invasion of cancer cells. In glioblastoma, control of cytoskeletal dynamics has been attributed to the orchestrated activity of several signaling pathways, including Rac1, RhoA, and RhoC (45)(46)(47). Interestingly, the two latter pathways have also been implicated in c-Jun regulation (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms underlying these effects are not entirely clear, the integrity of the microtubule network is a well-established player in controlling the balance of Rho GTPase activities and, therefore, F-actin assembly and actomyosin contractility in 2D cultures (Etienne-Manneville, 2013). Interestingly, specific cell types, such as glioblastoma cells have been reported to be actin independent but require microtubules for migration in 2D (Panopoulos et al, 2011). …”
Section: Introductionmentioning
confidence: 99%